A Porphyrin‐Based Porous rtl Metal–Organic Framework as an Efficient Catalyst for the Cycloaddition of CO2 to Epoxides. Issue 47 (12th October 2016) - Jiang, Wei; Yang, Jin; Liu, Ying‐Ying; Song, Shu‐Yan; Ma, Jian‐Fang
Abstract: A porous rtl metal–organic framework (MOF) [Mn5 L(H2 O)6 ⋅(DMA)2 ]⋅5DMA⋅4C2 H5 OH (1⋅ Mn) (H10 L=5, 10, 15, 20‐tetra(4‐(3, 5‐dicarboxylphenoxy)phenyl)porphyrin; DMA= N, N ′‐dimethylacetamide) was synthesized by employing a new porphyrin‐based octacarboxylic acid ligand.1⋅ Mn exhibits high Mn II density in the porous framework, providing it great Lewis‐acid heterogeneous catalytic capability for the cycloaddition of CO2 with epoxides. Strikingly, 1⋅ Mn features excellent catalytic activity to the cycloaddition of CO2 to epoxides, with a remarkable initial turnover frequency 400 per mole of catalyst per hour at 20 atm. As‐synthesized1⋅ Mn also exhibits size selectivity to different epoxide substrates on account of their steric hindrance. The high catalytic activity, size selectivity, and stability toward the epoxides on catalytic cycloaddition of CO2 make1⋅ Mn a promising heterogeneous catalyst for fixation and utilization of CO2 . Abstract : The porphyrin‐based porous rtl metal–organic framework1⋅ Mn features high catalytic activity, size selectivity, and stability toward the cycloaddition of CO2 to epoxides. These features make1⋅ Mn a promising heterogeneous catalyst for fixation and utilization of CO2 .